Rendimento e composição química do óleo essencial de raízes de Piper gaudichaudianum Kunth e atividade fungitóxica in vitro - Tres, Jesica (2017)
The objective of this work was to quantify the yield and to analyze the chemical composition of the essential oil of roots of Piper gaudichaudianum Kunth in a population of Santa Maria, RS, Brazil, as well as to verify the possible influence of the seasonality on these parameters. In an experimental assay, the in vitro fungitoxic activity of the essential oil as well as of its major component was verified, against the wood rotting fungi Trametes versicolor and Gooeophyllum trabeum. The plant material was collected in the four seasons of ayear and the essential oil was extracted from fresh roots by hydrodistillation using Clevenger apparatus for 3 hours. The yield of the essential oil was determined as percentage, considering the mass of the extracted plant material (% m m-1). Its chemical composition was determined by gas chromatography coupled to mass spectrometry (GC-MS), and gas chromatography with flame ionization detector (GC-FID). For the definition of chemical groups, the constituents present in the extractive in percentages > 1% were considered, using Hierarchical Cluster Analysis (HCA) and Principal Component Analysis (PCA). The major component was isolated by column chromatography and was identified with the aid of spectroscopic methods. The fungitoxic activity was evaluated by dilution in PDA (potato-dextrose-agar) medium. Initially the essential oil and its major substance were diluted in ethanol (1: 1), followed by addition of the solutions to the medium, at the final concentrations of 0.0 (negative control), 0.25; 0.5 and 1.0 μL/mL, and 1.0 μL/ mL in the case of the major constituent. Propiconazole was used as a positive control (1.0 μL/mL). The average yield values of the essential oils did not differ between seasons, ranging from 0.07% to 0.09%. The chemical characterization of extractives allowed to identify the major constituent as 4-(3-hydroxy-3-methyl-butenyl)-methylbenzoate, a benzoic acid derivative with average values ranging from 62.55% to 70.23%. The multivariate analysis allowed to detect differences in the essential oil composition of the seasons spring and summer to autumn and winter. The fungitoxic activity of the essential oil was concentration dependent and varied according to the fungal species tested. The activity of the major constituent did not differ from that of the essential oil and the positive control for T. versicolor, but was lower than that of essential oil and propiconazole in the case of G. trabeum. Both the essential oil and its major component have fungitoxic potential at the maximum concentrations evaluated, 0.5 e 1.0 μL/mL..